Transgenic Tomato Plants Overexpressing Tyramine N -Hydroxycinnamoyltransferase Exhibit Elevated Hydroxycinnamic Acid Amide Levels and Enhanced Resistance to Pseudomonas syringae - Campos, Laura; Lisón, Purificación; López-Gresa, María Pilar; Rodrigo, Ismael; Zacarés, Laura; Conejero, Vicente; Bellés, José María (Molecular plant-microbe interactions, 2014)
Hydroxycinnamic acid amides (HCAA) are secondary metabolites involved in plant development and defense that have been widely reported throughout the plant kingdom. These phenolics show antioxidant, antiviral, antibacterial, and antifungal activities. Hydroxycinnamoyl-CoA:tyramine N-hydroxycinnamoyl transferase (THT) is the key enzyme in HCAA synthesis and is induced in response to pathogen infection, wounding, or elicitor treatments, preceding HCAA accumulation. We have engineered transgenic tomato plants overexpressing tomato THT. These plants displayed an enhanced THT gene expression in leaves as compared with wild type (WT) plants. Consequently, leaves of THT-overexpressing plants showed a higher constitutive accumulation of the amide coumaroyltyramine (CT). Similar results were found in flowers and fruits. Moreover, feruloyltyramine (FT) also accumulated in these tissues, being present at higher levels in transgenic plants. Accumulation of CT, FT and octopamine, and noradrenaline HCAA in response to Pseudomonas syringae pv. tomato infection was higher in transgenic plants than in the WT plants. Transgenic plants showed an enhanced resistance to the bacterial infection. In addition, this HCAA accumulation was accompanied by an increase in salicylic acid levels and pathogenesis-related gene induction. Taken together, these results suggest that HCAA may play an important role in the defense of tomato plants against P. syringae infection.